PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH PADA PEGADAIAN SYARIAH UNIT BANYUWANGI - Samsuri Samsuri; Guritno Prihatmojo Wisnu Murti (Program Studi Ekonomi Syariah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2021)
This study aims to determine whether there is an influence of service quality on customer loyalty at the Banyuwangi Syariah Pawnshop Unit. This research is a quantitative research. The population of this research is the customers of Pawnshop Syariah Unit Banyuwangi, where the sampling is 100 customers. Data was collected using a questionnaire method for service quality instruments. The analysis of the two instruments includes the analysis of validity and reliability. The data analysis method used is multiple linear regression analysis technique using SPSS 18 for windows 10. The results of the validity analysis show that from 5 variables proved valid, all of them are reliable. Judging from the acquisition of f arithmetic > f table (48.357>2.31), while the results of the regression equation y = -6.314+0.235X1+ 0.173X2+0.038X3+0.129X4+0.165X5 and the results of the t-test of 4 variables obtained t-count > t- table (3.131, 2.151, 2.667, 3.221 >1.98552) and 1 variable that results in t count < t table (0.623 <1.98552) it can be seen that there are 4 variables that affect customer loyalty and 1 variable does not affect customer loyalty. The influence is included in the very strong category obtained from the multiple correlation coefficient data of 0.849, which is between the values ​​of 0.800-0.999. And it means Ha is accepted and Ho is rejected. Thus, it can be concluded that there is an influence of service quality on customer loyalty at the Banyuwangi Syariah Pawnshop Unit.